CD36 AA genotype is associated with decreased lipid taste perception in young obese, but not lean, children - Sayed, A; Šerý, O; Plesnik, J; Daoudi, H; Rouabah, A; Rouabah, L; Khan, N A (International journal of obesity (2005), 2015)
BACKGROUND/OBJECTIVE: Obesity is an alarming threat for all age groups, including children. Fat overconsumption is one of the factors that directly influences this pathology. Recent studies have suggested that a common variant in the CD36 gene, that is, single-nucleotide polymorphism (SNP) rs1761667-A allele, that reduces CD36 expression, associates with high oral fat detection thresholds in some obese subjects. The objective was to assess fatty acid sensitivity in relation to CD36 SNP in young lean and obese children. SUBJECTS/METHODS: We studied lingual detection thresholds for emulsions, containing oleic acid, in Algerian children (n=116, age=8±0.5 years) who were divided into two groups: obese (n=57; body mass index (BMI) z-score=2.513±0.490) and lean children (n=59; BMI z-score=-0.138±0.601) by alternative-forced choice method. To correlate the lipid taste perception thresholds with CD36 SNP, the children were genotyped for A/G SNP rs1761667 in 5'UTR region of CD36 by using PCR and restriction fragment length polymorphism. RESULTS: We noticed significantly higher CD36 A-allele frequency (P=0.036) in young obese children compared with leans. CD36 A-allele was associated with higher lipid taste perception thresholds than G-allele in obese children, but not in lean controls. Moreover, waist circumference was positively correlated with reduced fat taste sensitivity in these children. CONCLUSIONS: CD36 SNP A-allele, being present both in young lean and in obese children, is associated with high threshold for fatty acid taste sensitivity only in obese children.
Keywords: preference v jídle; lidé; Obesity; Taste Perception; Polymorphism, Single Nucleotide; stravovací zvyklosti; Female; dítě; dietní tuky; průzkumy a dotazníky; Feeding Behavior; antigeny CD36; chuťová percepce; hubenost; Body Mass Index; Gene Frequency; jednonukleotidový polymorfismus; Humans; obvod pasu; index tělesné hmotnosti; Genotype; Oleic Acid; Algeria; obezita; Alžírsko; frekvence genu; mužské pohlaví; Thinness; ženské pohlaví; genotyp; Male; Food Preferences; Waist Circumference; kyselina olejová; Child; CD36 Antigens; Surveys and Questionnaires; Dietary Fats